Individual Differences in Facial Emotion Processing: Trait Emotional Intelligence, Cognitive Ability, or Transient Stress?. (February 2015) - Matthews, Gerald; Pérez-González, Juan-Carlos; Fellner, Angela N.; Funke, Gregory J.; Emo, Amanda K.; Zeidner, Moshe; Roberts, Richard D.
This study tested whether trait emotional intelligence (TEI) measures of narrow bandwidth predict perception of facial emotion, using two tasks: identification of microexpressions of emotion and controlled visual search for target emotions. A total of 129 undergraduates completed multiple scales for TEI, as well as cognitive ability, personality, and stress measures. TEI was associated with a reduced stress response, but failed to predict performance on either task, contrary to the initial hypothesis. However, performance related significantly to higher cognitive intelligence, subjective task engagement, and use of task-focused coping. Individual differences in attentional resources may support processing of both emotive and non-emotive stimuli.